Особливості заміни калориферної установки котла ТГМП-314 - Римар, Тетяна Іванівна; Заяць, Марія Федорівна (Національний технічний університет "Харківський політехнічний інститут", 2022)
Представлено результати реконструкції проектних калориферів котлів ТГМП-314 із секціями санітарно-технічних калориферів КФСО-ІІ і КФБО-ІІ на секції енергетичних калориферів (СО-110). Послідовне встановлення стінок калориферів підвищує коефіцієнт теплопередачі приблизно в 1,6 рази порівняно з паралельним включенням, що за однакової кількості секцій дає можливість збільшити швидкість повітря в калориферах вдвічі, а також підвищує рівномірність температурного поля в коробі перед РПП.

Thermal power stations play the main role not only in carrying the base load, but also in ensuring the coverage of peak and semi-peak loads of electricity consumption. Improving the operational maintenance of energy equipment gives a greater economic effect, since the costs of modernization of regenerative air heaters, which improve their density and thermal efficiency, are repaid in a short time. The efficiency and cost-effectiveness of the operation of regenerative air heaters was increased by the reconstruction of the heating installation. The results of the reconstruction of the design heaters of the TГМП-314 boilers with sections of sanitary-technical heaters КФСО-II and КФБО-II with replacement by sections of energy heaters (СО-110) are presented. The improved heating installation is installed in front of each regenerative air heater of the ТГМП-314 boiler and is made of two walls placed sequentially according to the air movement, in each of which 12 sections of reconstructed CO-110 heaters with a downward movement of the heating steam flow are installed. An important advantage of the proposed sequential installation of radiators is an increase in the uniformity of the temperature field in the box in front of the regenerative air heater due to two-stage air heating. Sequential installation of radiator walls increases the heat transfer coefficient approximately 1.6 times compared to parallel connection, which makes it possible to double the air speed in the radiators for the same number of sections. The possibility of formation of stagnant zones of sections of CO-110 heaters is excluded. In this case, it is recommended to reconstruct single-pass radiators with the installation of a pipe board and heating steam condensate removal chambers. The high efficiency of the improved heating installation made it possible to carry out all boiler ignitions with the possibility of supplying flue gases immediately through the RAH.
Features of replacement of the ТГМП-314 boiler heating installation
Keywords: котел; калорифер; повітропідігрівник; турбіна; паливо; температура; навантаження; boiler; calorifier; air heater; turbine; fuel; temperature; load